What Are Inert Ingredients? - Frederick M. Fishel (EDIS)
This guide addresses inert ingredients that are contained in pesticide product formulations. This document is PI-44, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.